2020
DOI: 10.3390/microorganisms8122023
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Microbial Community and Metabolites in Litter Layer of Plantation and Original Korean Pine Forests in North Temperate Zone

Abstract: In order to explore the relationship between microbial diversity and metabolites in the litter layer of northern temperate forests, the microbial community structure and metabolite species in the litter layer of an original Korean pine forest and Korean pine plantation of northern temperate climate were determined on the basis of high-throughput sequencing and metabonomic techniques. The results showed that there were 698 bacterial genera and 363 fungal genera in the litter samples in the original Korean pine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Most of the novel putative degraders were members of Candidatus Rokubacteria in our search and contained representatives from marine, freshwater, soil, subsurface, and sediment environments. This observation is consistent with previous reports of the global diversity of Rokubacteria (46), which are also expected to play an important role in sulfur cycling (47,48) and degradation of complex carbon compounds found in leaf litter or root exudates (48)(49)(50). Previous work demonstrating uncultured microbes like Rokubacteria may use alternative metabolic pathways that prevent their culturing under typical conditions (46,51,52) highlights the power of non-culture-based methods in exploring community structure and function and the limits of historic cultured-based primer development methods for environmental analyses.…”
Section: Resultssupporting
confidence: 93%
“…Most of the novel putative degraders were members of Candidatus Rokubacteria in our search and contained representatives from marine, freshwater, soil, subsurface, and sediment environments. This observation is consistent with previous reports of the global diversity of Rokubacteria (46), which are also expected to play an important role in sulfur cycling (47,48) and degradation of complex carbon compounds found in leaf litter or root exudates (48)(49)(50). Previous work demonstrating uncultured microbes like Rokubacteria may use alternative metabolic pathways that prevent their culturing under typical conditions (46,51,52) highlights the power of non-culture-based methods in exploring community structure and function and the limits of historic cultured-based primer development methods for environmental analyses.…”
Section: Resultssupporting
confidence: 93%
“…The sequences of seven endophytic bacteria were deposited at the GenBank with accession numbers (MW759557-MW759563). Previous research has shown that these bacteria are isolated and identified from different hosts (Zhang et al, 2014;Battu et al, 2017;Wang et al, 2020;Cheng et al, 2021). However, these genera were not found in the Phormodium sp.…”
Section: Resultsmentioning
confidence: 95%
“…LEfSe analysis showed that Proteobacteria had the highest contribution to the soil bacterial community in winter, which was related to the high hemoglobin content in the topsoil layer. Proteobacteria use hydropyrite as an electron acceptor to drive iron ore reduction under an anoxic environment and reduce iron-containing organic matter to ferrous atoms, resulting in an increase in heme content (Wang et al, 2020 ). The relative abundance of Proteobacteria significantly increased in winter and significantly decreased in summer, while the relative abundance of Planctomycetes showed the opposite trend.…”
Section: Discussionmentioning
confidence: 99%